Soil carbon stocks and soil solution chemistry in Quercus ilex stands in Mainland Spain - González González, I.; Grau Corbí, J. M.; Fernández Cancio, a; Jiménez Ballesta, R.; González Cascón, M. R. (European Journal of Forest Research, 2012)
The quantiﬁcation of terrestrial carbon pools is important for the modeling of carbon ﬂuxes in forest ecosystems. As a contribution to the understanding of the factors that inﬂuence the carbon sequestration capacity of Mediterranean forest soils, the present study focuses on the quantiﬁcation of the superﬁcial soil carbon stocks in evergreen oak stands (Quercus ilex L.) representative of its distribution area in Mainland Spain and to analyze the inﬂuence of site factors (climate and topography) and the soil chemical properties in the topsoil carbon storage capacity. For that purpose, 103 Quercus ilex stands were studied grouped in four main formations: 40 wooded grassland ecosystems with scattered oak trees (dehesas), 14 open Holm oak stands, 28 mixed Holm oak forests and 21 dense Holm oak forests. The soil organic carbon stocks (SOCS) in the upper organo-mineral soil layer ranged between 1.4–15.6 kg m -2 and total soil carbon stocks (TSCS) between 1.4–17.9 kg m -2 . Tree density was a signiﬁcant factor for SOC storage in the soil. The wooded grassland dehesas presented the minimum superﬁcial SOC stocks (3.6 kg m -2 ), while dense Holm oak forests reached the maximum average values (7.6 kg m -2 ). Maximum SOCS ([10 kg m -2 ) were measured in the mixed and dense Holm oak forests over soils with calcareous substrates. Summer mean temperature (R = -0.46; P\0.001) was the climatic variable that most inﬂuenced the SOCS. Soil properties had stronger positive correlations with SOCS than site factors: nitrogen concentrations (R = 0.70; P\0.001), clay content (R = 0.62; P\0.001), soluble calcium (R = 0.60; P\0.001) and magnesium (R = 0.42; P\0.001). Climatic and topographic variables together explained 30 % of the SOCS variability. An increase up to 63 % was obtained by including soil variables. Under Mediterranean climate conditions, the soil properties that enhance the organic matter protection achieve a notable relevance. The soil carbon storage is favored by large organic matter inputs, high soil clay contents, a calcium-saturated soil matrix and reduced summer aridity.
Keywords: Dehesa; Mediterranean ecosystems; mediterranean ecosystems á soil; Quercus ilex; quercus ilex á; soil carbon stocks; soil carbon stocks á; soil solution; solution á dehesa

Precipitation, throughfall, soil solution and streamwater chemistry in a holm-oak (Quercus ilex) forest - Rodà, Ferran; Avila, Anna; Bonilla, David; Rodà, Ferran (Journal of Hydrology, 1990)
Bulk precipitation, throughfall, soil solution at 20 and 40 cm depths, and stream water were monitored for 2–4 years in a holm-oak forest on schists in the Montseny Mountains (NE Spain). Bulk precipitation was mildly acidic, with Ca2+ and SO2−4 as dominant ions. Canopy interactions produced a throughfall less acidic than bulk precipitation and enriched in all other ions. Large amounts of K+ were leached from the canopy. Magnesium in net throughfall behaved similarly to K+, and it is concluded that leaching makes a major contribution to Mg2+ enrichment beneath the canopy. Judging from the moderate increase of Na+ and Ca2+ in throughfall, dry deposition rates for both marine and continental aerosols were low in the studied stand, probably because of its sheltered topographic position within a well-vegetated massif, coupled with moderate tree height and low canopy roughness. Soil solution in the mineral soil was less acidic than throughfall. In common with most temperate forests, SO2−4 was the dominant mobile anion in the soil water, being largely accompanied by Ca2+. Potassium and NO−3 were depleted within the soil water with respect to throughfall, probably owing to biological uptake and cation exchange, and incorporation of K+ into clay lattices. Subsurface flow dominated the hydrology of the small forested catchment studied. Stream water was basic and rich in bicarbonate. Its chemistry revealed fast rates of weathering of sodium- and magnesium-bearing silicates (mainly albite and chlorite, respectively). Soil respiration and silicate hydrolysis resulted in HCO−3 being the dominant mobile anion in stream water. Calcium to chloride ratios were similar in bulk precipitation and in stream water, indicating that Ca2+ release from weathering has been counteracted by plant uptake. Nutrient uptake by this aggrading forest strongly influences the solution dynamics of K+, NO3 and Ca2+. It is concluded that: (1) this forest does not currently receive acidic atmospheric deposition; (2) the neutralization capacity of the soil-bedrock system is quite high; (3) biotic regulation and silicate weathering are the major processes shaping the solution biogeochemistry in this Mediterranean forest ecosystem.
Keywords: Canopy; chemistry (voyant); Holm oak; Montseny mountains; Precipitation; soil solution; stream water; throughfall